A Fluorescent and Colorimetric Sensor for Nanomolar Detection of Co2+ in Water. Issue 18 (15th October 2014) - Kuwar, Anil; Patil, Rahul; Singh, Amanpreet; Bendre, Ratnamala; Singh, Narinder
Abstract A new disulfide‐based, imine‐linked fluorescent receptor 1 was processed into organic nanoparticles (ONPs) with an average particle size of 79 nm. The photophysical properties of the ONPs were evaluated by UV/Vis absorption spectroscopy. Receptor 1 selectively recognized Co2+ ions in water with a detection limit down to 88 nm.